Rancang Bangun Sitem Manajemen Ruang Menggunakan Sensor PIR untuk Kontrol Saklar Otomatis dan Penghemat Energi - Rahmawati, Lia; Setyawan, Galih (Jurnal Fisika Unand, 2025)
High electricity consumption not only increases electricity bills but also contributes to the energy crisis, especially with the rising base rates of kWh from PLN. Thus, optimizing energy usage is crucial. This study aims to develop a room management system that optimizes power consumption through an automated on-off switch, controlling lights and fans based on the number of people detected in the room. The system also offers the potential to estimate the need for assistance during natural disasters. The research methodology includes system design, prototype development, and system testing. Two Passive Infra Red (PIR) sensors are placed on either side of the door to detect the movement of people entering and exiting. Test results indicate that the PIR sensors provide 100% accuracy, with a maximum detection angle of 40 degrees and a range of 7 meters. The system is able to reduce energy consumption by up to 66%, with a power usage of 18.24 watts over 3 hours, compared to 27.36 watts without the system. The system interface was developed using Processing to display the sensor detection results.